OpenCL in action : how to accelerate graphics and computation - Scarpino, Matthew, 1975- (Manning, 2012)
OpenCL (Open Computing Language) helps developers build high-performance applications by providing a single programming framework to build programs that execute on today's high-speed devices. Based on C and C++, it's a perfect tool to build number-crunching applications for graphics cards and multi-core processors. OpenCL in Action provides a thorough, hands-on presentation of OpenCL, with an eye toward showing developers how to build high-performance applications of their own. It begins by presenting the core concepts behind OpenCL, including vector computing, parallel programming, and multi-threaded operations. It explains the fundamental data structures of OpenCL in an intuitive manner, proceeding from the simple to the complex. Practical coding guidance is presented throughout, with loads of valuable techniques and code examples included.